2012
DOI: 10.1345/aph.1r028
|View full text |Cite
|
Sign up to set email alerts
|

Generic Immunosuppression: Deciphering the Message Our Patients are Receiving

Abstract: Patient ethnicity, income, and experience with generic immunosuppressants appear to contribute to perceptions of generic immunosuppressants. The prevalence of generic immunosuppressant use supports the importance of communication of this issue between providers and patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…A survey in the UK showed that 84% of renal transplant patients felt that generics are not equivalent or only equivalent sometimes and that they were uncertain that generics had the same quality as branded medicines . In the US, a survey among 255 transplant recipients showed that 81 patients (32%) had been converted to a generic immunosuppressant, but 25% of converted patients did not believe that there was equivalence between generic and brand products . When patients are not allowed to choose freely, this may affect their adherence to medication, intentional, or unintentional, potentially influencing clinical outcome.…”
Section: The Perspective Of the Patientmentioning
confidence: 99%
“…A survey in the UK showed that 84% of renal transplant patients felt that generics are not equivalent or only equivalent sometimes and that they were uncertain that generics had the same quality as branded medicines . In the US, a survey among 255 transplant recipients showed that 81 patients (32%) had been converted to a generic immunosuppressant, but 25% of converted patients did not believe that there was equivalence between generic and brand products . When patients are not allowed to choose freely, this may affect their adherence to medication, intentional, or unintentional, potentially influencing clinical outcome.…”
Section: The Perspective Of the Patientmentioning
confidence: 99%
“…Medications: Exposing the lung transplant recipient to different generic formulations of a particular immunosuppressant medication could result in adverse outcomes because of the potential variation in their pharmacokinetic effects and drug-drug interactions. 114,115 The International Society for Heart and Lung Transplantation recommends that 114 (1) patients inform their care coordinators of any potential generic drug substitution of their immunosuppressant medications, (2) generic immunosuppressants should be used with a high degree of caution, and (3) surveillance strategies and frequent TDM should be implemented until stable immunosuppression is achieved.…”
Section: Caution With Generic Substitution Of Immunosuppressantmentioning
confidence: 99%
“…[12][13][14][15][16][17] The same increased intrapatient variability was associated with poorer patient outcomes and greater treatment costs. A subsequent large retrospective study from the Collaborative Transplant Group showed that a group of 397 patients receiving generic cyclosporine had a trend toward overall poorer graft survival compared to the 17,198 patients receiving branded cyclosporine.…”
Section: Article In Pressmentioning
confidence: 99%